White rot fungus mediated removal of mercury from wastewater. (21st July 2022) - Sharma, Kalu Ram; Naruka, Anjali; Raja, Manokaran; Sharma, Rakesh Kumar
Abstract: Heavy metal contamination creates numerous problems in environment and considered as big challenge for the society. Mercury (Hg) may exert several harmful effects on human heath including nervous system, digestive system, and immune system, along with damage in lungs and kidneys, which might be fatal. In this study, the removal of Hg from the wastewater by using a whiter rot fungus Phlebia floridensis was evaluated in a batch culture system for 7 days. The fungus was also evaluated for the tolerance level of Hg and the morphological changes were studied by SEM–EDX. The fungus could tolerate up to 100 μM of Hg concentration. Scanning electron microscopic images showed changes in the morphology and fine structures of the fungal hyphae. Atomic absorption spectroscopic analyses of the treated water sample revealed that the fungus could remove 70%–84% of Hg depending upon the initial concentration. The pH fluctuation was recorded from 5.8 to 6.8 during the experimental conditions at temperature 28°C ± 2°C. Thus, the study explores the use of this fungus for the application in metal containing wastewater treatment. Practitioner Points: Hg contaminated water can be treated by using white rot fungus, Phlebia floridensis . The fungus may accumulate mercury inside as well as on the surface of fungal mycelial biomass. Change in hyphal morphology was observed in the presence of lower concentration of the metal. Abstract : Hg contaminated water can be treated by using white rot fungus, Phlebia floridensis . This fungus may accumulate mercury inside as well as on the surface of fungal mycelial biomass. As observed under SEM, a hyphal thickness was observed in the presence of lower concentration of the metal. EDX and AAS was used to detect the Hg content on cell surface as well as in treated water samples.